INOVASI PRODUK RENDAH KALORI: PENGEMBANGAN UMKM D'ROOSE CAKE DENGAN PEMANIS ALAMI STEVIA DI KOTA PADANG - Daimon Syukri; Rini Bahar; Ratni Prima Lita; Wellyalina Wellyalina; Novelina Novelina; Purnama Dini Hari; Rina Yenrina; Kesuma Sayuti; Tuty Anggraini; Aurelia Amaliyah Tarumiyo; Yasmin Azzahra (LPPM Universitas Andalas, 2025)
The purpose of the service activity is to innovate D'Roose Cake products into functional cakes that can create opportunities and ace cards for D'Roose Cake businesses that can adjust the development and demand for healthy products that are currently trending in the market. The research conducted was qualitative by conducting a case study of innovative products using stevia. The implementation was carried out in three stages, first the preliminary stage where socialization and discussion with partners were carried out regarding the objectives, targets, and outcomes of the program. Second, the implementation stage, conducting research and modifications to existing product recipes, namely banana sponge cake. Third, the evaluation stage, at this stage an evaluation of public acceptance of the innovative product is carried out. The results of this activity increased production capacity through upgrading the baking equipment or oven. After upgrading the equipment, it can now produce 150 loaves of bread in ± 4 hours. Then the innovative products were tried to the market at the Car Free Day activity at Gor H. Agus Salim, getting a good consumer response. The conclusion of this activity is that UMKM D'Roose Cake is one of the cake and bakery industries that has a P-IRT distribution permit and is halal certified. The constraints faced by these MSMEs are limitations in production capacity. In response to this, efforts were made to develop the production of D'Roose Cake MSME products through increasing the capacity of production equipment and developing stevia-based products.